Implementation Of The Values Of The 8 Rukuns Of Students In Character Internalization At The SPMAA Islamic Boarding School In Turi Lamongan - Nadira Eka Palupi; Jasminto Jasminto (AR-RASYID : Jurnal Pendidikan Agama Islam, 2026)
This research aims to describe the form of the 8 Santri Pillars at Pondok Pesantren SPMAA Turi Lamongan and analyze their implementation in forming student character. This study also identifies supporting and inhibiting factors in the implementation process of these spiritual guidelines. The research uses a qualitative approach with a descriptive field research type. Data were collected through participant observation, in-depth interviews with caregivers, teachers, and students, and documentation studies. The subjects were determined using purposive sampling to ensure data credibility. Data analysis followed the stages of reduction, data display, and conclusion drawing, with validity guaranteed through source and method triangulation. The results show that the 8 Santri Pillars consist of congregational prayers, tahajud, dhuha, sunnah fasting, Quranic and Hadith studies, general lectures, and holy reflection. These practices serve as a structured spiritual system that internalizes values of discipline, independence, and responsibility. Character formation occurs through consistent habituation and continuous spiritual training rather than mere cognitive instruction.